Enhancing Students’ Understanding of Spatial Nets through Problem-Based Learning Integrated with Two Stay Two Stray - Akyun, Qurrotun; In’am, Akhsanul; Rosyadi, Alfiani Athma Putri (Department of Mathematics Education University of Muhammadiyah Malang, 2025)
This study aims to implement spatial net learning based on Problem-Based Learning (PBL) integrated with the Two Stay Two Stray (TSTS) strategy for ninth-grade junior high school students. The learning was conducted through an open class approach in three Plan–Do–See cycles, focusing sequentially on flat-sided nets, curved-sided nets, and their combinations. Learning implementation was observed using the Basic Teaching Skills (KDM) instrument, while student outcomes were evaluated in terms of attitude, skills, and knowledge. The results show that learning implementation consistently reached an excellent category, with scores ranging from 96.43% to 97.72%. Students’ attitudes improved from 94.4% in the first cycle to 100% in the second and third cycles. Skill performance increased significantly in the second cycle (98.3%) and slightly decreased in the third cycle (96.6%) as task complexity increased. Knowledge scores also rose from 90 to 95.5 before slightly declining to 93.3 in the final cycle. These findings indicate that improvement occurred because contextual problem-solving in PBL, combined with structured cross-group idea exchange through TSTS, supported students’ visual spatial reasoning and conceptual understanding of spatial nets. Overall, this study demonstrates that integrating PBL and TSTS provides a pedagogically meaningful approach for geometry learning that emphasizes exploration, visualization, and collaborative reasoning.